Cambios en la percepción y el sentido de la historia (Nueva España, 1816-1820) - Ibarra, Ana Carolina (El Colegio de México, A.C., 2013)
The paper seeks to explain the paths that gave way to a new vision of the past, a more rigorous and modern vision, but also more useful to the demands of the present time. Particularly, the author examines three texts that circulated in New Spain on the eve of the consummation of independence and whose appearance allows to establish a connection between the late 18th century historiography, the discourses of independence, and what some people called “contemporary history”. Based on these leaflets, a relation can be established between the debates that took place within the learned milieux and the spaces of a public opinion that was expanding its margins during that period.